History of Muhammadiyah: An Islamic Reform Movement in Indonesia - Rudy Herlambang; Mappanyompa (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Muhammadiyah is one of the largest Islamic organizations in Indonesia founded by K.H. Ahmad Dahlan in 1912. This organization emerged as a response to the religious practices of Muslims at that time that were mixed with local traditions that were not in accordance with the principle of tawhid. This article discusses the background of the establishment of Muhammadiyah, its vision and mission as a tajdid movement, and its contributions in education, social, and religious affairs in Indonesia. Utilizing a historical approach, this paper shows that Muhammadiyah is not only a religious movement but also plays an important role in the social reform of society.